Teachers’ Strategies in Cultivating Islamic Moral Character through Aqidah Akhlaq Learning in Islamic Primary Schools - Mukarromah, Lailatul; Fahmi, Robith (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study examines teachers’ strategies in cultivating Islamic moral character through Aqidah Akhlaq learning at an Islamic primary school. The research employed a descriptive qualitative approach involving Aqidah Akhlaq teachers, the madrasah principal, and students as research participants. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that teachers implemented several interconnected strategies to cultivate students’ akhlaqul karimah, namely habituation practices, role modelling (uswatun hasanah), reward and punishment, motivational guidance, and the integration of moral values into the learning process through storytelling, discussion, and simulation methods. Among these strategies, habituation and teacher exemplarity were found to have a greater influence on students’ moral behavior than formal cognitive instruction alone. The study also found that a supportive madrasah environment and parental involvement strengthened the implementation of moral education, whereas limited parental supervision and negative influences from social media and digital technology became major obstacles. This study contributes to the discourse on Islamic character education by highlighting the importance of integrating instructional, cultural, and relational approaches in cultivating moral character at the primary education level. However, the findings are limited to a specific institutional context and cannot be generalized broadly. Further studies involving wider educational settings are therefore recommended.